2019
DOI: 10.1016/j.tics.2019.02.003
|View full text |Cite|
|
Sign up to set email alerts
|

How Efficiency Shapes Human Language

Abstract: Cognitive science applies diverse tools and perspectives to study human language. Recently, an exciting body of work has examined linguistic phenomena through the lens of efficiency in usage: what otherwise puzzling features of language find explanation in formal accounts of how language might be optimized for communication and learning? Here, we review studies that deploy formal tools from probability and information theory to understand how and why language works the way that it does, focusing on phenomena r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(245 citation statements)
references
References 127 publications
(161 reference statements)
8
196
3
Order By: Relevance
“…Furthermore, the gestures were coded for the amount of marking for the functional category, and this showed that such gestures occurred more often at later generations. Finally, average gesture duration -as a measure of communicative efficiency -did not reliably change over the generations, which ran counter to predictions that more mature communication systems tend towards maximal efficiency (Gibson et al, 2019).…”
Section: While Gestures Have Their Natural Tendencies Of Expressioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Furthermore, the gestures were coded for the amount of marking for the functional category, and this showed that such gestures occurred more often at later generations. Finally, average gesture duration -as a measure of communicative efficiency -did not reliably change over the generations, which ran counter to predictions that more mature communication systems tend towards maximal efficiency (Gibson et al, 2019).…”
Section: While Gestures Have Their Natural Tendencies Of Expressioncontrasting
confidence: 74%
“…Based on the full sequences of the referential components that were uniquely expressed in each gesture, entropy was computed, which expresses compressibility of the gesture content, i.e., the amount of information that is needed to compress the signal. When a lot of referential components in the gesture utterance recurs between other gestures, the system has a more simple structure and indicates systematic reuse of gestural components (e.g., Gibson et al, 2019). Dovetailing with the qualitative observations and other studies in this field (e.g., Verhoef et al, 2016), it was found that gesture-component entropy decreased over the generations.…”
Section: While Gestures Have Their Natural Tendencies Of Expressionmentioning
confidence: 54%
See 1 more Smart Citation
“…When claims are made about ambiguity being beneficial for communicative efficiency, the domain of inquiry is typically restricted to a small range of ambiguities, like simple forms of polysemy or basic forms of syntactic ambiguity (as in Gibson et al 2019 and their focus on why SVO syntax might be more communicatively efficient than SOV syntax), ignoring more complex polysemy (e.g. copredication; Collins 2017) and syntactic phenomena (e.g.…”
Section: (7)mentioning
confidence: 99%
“…To investigate the computational plausibility of this potential gain in communicative efficiency we present a theoretical analysis of other-initiated repair and pragmatic reasoning. Following Gibson et al (2019), we define efficient communication as communication in which participants reach mutual understanding while requiring minimal effort in terms of resource costs (deconstructed here as the sum of computational and interactional cost). We compare a novel agent-based model of otherinitiated repair with one of pragmatic reasoning (Goodman and Frank, 2016) for both their communicative success and use of computational and interactional resources.…”
Section: Introductionmentioning
confidence: 99%